Divine Apriori Knowledge in the Mulla Sadra and Avicenna Wisdom and its Comparison to Verses and Tradition - Abbas Hajiha; Mohammad Reza Zamiri; Yadullah Dadjou; mohammad allahi (حکمت صدرایی, 2018)
This paper, using the integrative method (rational, narrative) and bibliographic and documental and library references, has examined the comparative study of divine knowledge in the wisdom of  Mulla Sadra and Avicenna and its comparison to verses and narratives, and seeks to explain and adapt the views of two famous philosophers, Avicenna and Mulla Sadra, about the divine a prior knowledge. The findings indicate that in the wisdom of Mulla Sadra, knowledge is an existential and hierarchal process, and in peripatetic philosophy, a quality of soul. In the transcendent wisdom, God's knowledge to the nature and knowledge to the beings, before and after the creation, is a knowledge by presence, but in peripatetic philosophy, the knowledge of the essence to essence and the knowledge of the forms, is a knowledge by presence and knowledge of the external things, beings before and after creation, is attainable knowledge. According to the image that Avicenna offers about the knowledge by presence about God, the God, before the creation of the forms, did not have knowledge to the creatures, and this way of ignorance is considered in the essence of God, but in the verses and tradition, the knowledge of God has been known to his essence in any matter that exists, that knowledge also exists, whether there are theological forms or not. Sadra's theory, contrary to Avicenna’s command theory, has full coordination with verses and tradition and has been confirmed.